Some Remarks on the Use of Galician Language Within the Bussiness Sector in the 20th Century - Formoso Gosende, Valentina (Madrygal. Revista de Estudios Gallegos, 2004)
This article intends to describe the situation of the Galician language within the business sector nowadays, analising its original status before the current period of autonomous administration in Galicia and the achievements obtained throughout this period. The intention is to encourage reflection on the course followed by linguistic standardisation in this field and how much remains to be accomplished.